Progressive damage in pretensioned and reinforced concrete plates against repeated impacts. Issue 1 (March 2023) - Kumar, Vimal; Iqbal, Mohd. Ashraf; Mittal, Achal Kumar
This study is planned to explore the performance of pretensioned concrete (PC) plates under multiple impacts. A detailed investigation has been carried out on pretensioned concrete plates (0.8 × 0.8 m 2 ) against drop impact. The plates prepared using Mix-40 and Mix-60 grade concrete have been induced with two different levels of initial prestress, that is, 1/10 and 1/5 (i.e. level-1 and level-2) times the strength of the concrete. The PC plates have been impacted by a falling impactor (2382 N) dropped from 0.5 m height. The response of those plates has been obtained and compared with the reference RC plates. The post-impact performance of the damaged plates has been further discovered by subsequently dropping the impactor multiple times from the identical height. The FE simulations of the problem have been carried out using Johnson-Holmquist-2 and metal-plasticity constitutive models for concrete and steel, respectively. The models have been initially verified with the experimental results available in literature, and subsequently the simulations for drop impact have been carried out. The simulation results are also compared with the results of drop impact experimentations performed. In general, both the pretensioned and reinforced concrete have witnessed flexural cracks at the beginning, such that pretensioned concrete witnessed lesser cracks compared to reinforced concrete. As the number of drops increased, one major splitting crack developed only in pretensioned concrete, whereas the reinforced concrete exhibited additional punching cracks. For a given concrete grade, the pretensioned concrete level-2 witnessed the smallest damage, minimal cracks, and also minimal spalling followed by the pretensioned concrete level-1 and reinforced concrete. The reinforced concrete absorbed the minimal impact energy followed by the pretensioned concrete level-1 and level-2 under the multiple impacts. The FE simulations predicted the impact force and reaction within 11.9 and 9.9% variation, respectively, with the corresponding experimental results.